الأستاذ دلاور حسين سعيدي وإسهاماته في التفسير: دراسة تحليلية - حكيم، محمد فرقان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Ustaz Delawar Hossain Sayeedi spent valuable efforts to spread and preach Islam and the Holy Qur'an in various ways. He is well-known among Muslims and non-Muslims all over the world, especially in Bangladesh as a Mufassir al-Qur'an (Commentator of the Holy Qur'an). He has delivered Tafsir in many gatherings of innumerable masses, seminars and symposiums are arranged in different places in and out of the country. Thousands of people who attended his Tafsir programmes listen to his Qur'anic commentary to get good advice to implement in their everyday life. His Qur'anic commentaries are collected and preserved in CDs, VCDs and DVDs etc. He has written a few volumes of commentaries on some suras of the Qur'an. In this research, the researcher examines his written commentaries using three methods: descriptive, analytical and critical. This research contains references from the books of Ustaz Sayeedi and others related to it. His Tafsir is considered as very dynamic, social and reforming written in Bengali language. In this study, the researcher briefly describes his life and the methodology in this tafsir. Actually, Sayeedi followed two types of tafsir: al-Mathur and al-Rai'. The unique characteristic of his tafsir is being Tafsir al-Mawdui'. Firstly he identified verses or suras and translated them in Bengali. He labeled the main points of discussion with headlines in Bengali, explained according to the method of Tafsir al-Mawdui' and described the verses/suras followed by a summary of the verses. He also mentioned Ahadith (Prophetic Traditions) related to the subject. Sometimes he mentioned the historical events related to it. His Qur'anic commentary is understandable for people of all levels and people also understand his verbal commentary of the Qur'an whether educated or non-educated. It is mentioned that his verbal tafsir has a great impact on the minds of people who understand and practices them. He discussed the issues related to modern sciences that are mentioned in the Holy Qur'an in order to manifest the wisdom of the Almighty Allah as well as the miracle of the Prophet S.A.W. and the Holy Qur'an. To sum up, this tafsir can be considered as a Tafsir Haraki (dynamic Tafsir), Ijtimai' (social) and Islahi (reforming) as it conbines modern thinking with heritage Tafsir. It contributes a lot to the reformation of society and to establishing in men, tranquility and peace.